Measuring four facets of emotion beliefs in Germany: A German-language adaptation of the EBQ and its comparability across gender and different emotion abilities - Raphael Gutzweiler; David J. Grüning (PLoS ONE, 2025)
Adaptive emotion regulation, involving the modulation of positive and negative emotions based on goals, is a crucial function for a person’s mental health and general well-being. Factors influencing successful emotion regulation include beliefs about emotions, such as the controllability and usefulness of emotions. The Emotion Beliefs Questionnaire (EBQ) was developed to assess these beliefs and has shown promise in predicting emotion regulation and psychopathology across different countries. This study aims to advance EBQ’s generalizability in measuring emotion beliefs by examining the scale’s different validities for a developed German version. In a German sample of 348 respondents, we show the scale’s factorial and broader construct validity as well as its factors’ reliability. Notably, we demonstrate that the German EBQ is mostly strictly measurement invariant across central sociodemographic variables like age and gender. Interestingly, we also find the scale to be robust across different levels of other psychological constructs such as emotional reactivity and efficacy.